The Hemodynamic Effect of Enhanced External Counterpulsation Treatment on Atherosclerotic Plaque in the Carotid Artery: A Framework of Patient-Specific Computational Fluid Dynamics Analysis - Jianhang Du; Guangyao Wu; Bokai Wu; Chang Liu; Zhouming Mai; Yumeng Liu; Yawei Wang; Pandeng Zhang; Guifu Wu; Jia Liu (Cardiology Research and Practice)
Long-term enhanced external counterpulsation (EECP) therapy has been recommended for antiatherogenesis in recent clinical observations and trials. However, the precise mechanism underlying the benefits has not been fully clarified. To quantify the effect of EECP intervention on arterial hemodynamic environment, a framework of numerical assessment was introduced using a parallel computing algorithm. A 3D endothelial surface of the carotid artery with mild atherosclerotic plaque was constructed from images of magnetic resonance angiography (MRA). Physiologic boundary conditions were derived from images of the ultrasound flow velocity spectrum measured at the common carotid artery and before and during EECP intervention. Hemodynamic factors relating to wall shear stress (WSS) and its spatial and temporal fluctuations were calculated and analyzed, which included AWSS, OSI, and AWSSG. Measuring and computational results showed that diastole blood pressure, perfusion, and WSS level in carotid bifurcation were significantly increased during EECP intervention. Mean AWSS level throughout the model increased by 16.9%, while OSI level did not show a significant change during EECP. We thus suggested that long-term EECP treatment might inhibit the initiation and development of atherosclerotic plaque via improving the hemodynamic environment in the carotid artery. Meanwhile, EECP performance induced a 19.6% increase in AWSSG level, and whether it would influence the endothelial functions may need a further study. Moreover, the numerical method proposed in this study was expected to be useful for the instant assessment of clinical application of EECP .